2016
DOI: 10.1128/genomea.00554-16
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Microbacterium sp. Strain HM58-2, Which Hydrolyzes Acylhydrazides

Abstract: We report the draft genome sequence of Microbacterium sp. strain HM58-2, which produces hydrazidase, an enzyme hydrolyzing acylhydrazides. The estimated genome size is 3.9 Mb. Genome sequence information of this strain will help to identify an assimilating mechanism of nonnatural compounds in this strain and to develop ecological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In the course of the elucidation of the hydrazide metabolic pathway in Microbacterium sp. HM58-2, the whole genome sequence of the bacterium was obtained, and it was revealed that the hydrazidase gene is located in an operon with an IclR-type transcription factor, which is expected to control the gene expression of the operon (Akiyama et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the course of the elucidation of the hydrazide metabolic pathway in Microbacterium sp. HM58-2, the whole genome sequence of the bacterium was obtained, and it was revealed that the hydrazidase gene is located in an operon with an IclR-type transcription factor, which is expected to control the gene expression of the operon (Akiyama et al, 2016).…”
Section: Introductionmentioning
confidence: 99%